THE ROLE OF ASSISTANCE AND COLLABORATION IN INCREASING THE EFFECTIVENESS OF POLICY INNOVATION IN THE BANDUNG CITY GOVERNMENT - Dwi Purnomo; Wiedy Yang Essa; Yuliandri Rahadyanto; Ferdyansyah Wicaksono; Puntigavere Dante (Natapraja, 2025)
This study examines the role of assistance and collaboration in enhancing the effectiveness of policy innovation within the Bandung City Government. Amid rapid social and environmental changes, governments face increasing demands for innovative public services that address urban challenges and community needs. By employing a participatory assistance approach, this research evaluates the effectiveness of mentoring programs targeting regional apparatus organizations in Bandung, involving frameworks like Design Thinking and Theory of Change. Results indicate significant improvements in participants' understanding of regional innovation indicators, collaborative stakeholder engagement, and program evaluation methodologies. Despite progress, challenges persist, including structural barriers, limited resources, and cultural resistance to change. The findings highlight the need for leadership support, transparent regulations, and sustainable resource allocation to foster an innovation-friendly environment. This paper offers actionable policy recommendations to strengthen regional innovation and improve public service delivery in Bandung, setting a foundation for sustainable urban governance.